Imprensa, publicidade e educação : um estudo sobre a civilização dos costumes no interior do Brasil (Uberabinha, MG, 1919 - 1929) - Justino, Rogério (2016)
This research presents a brief study about the influence of advertisements in the civilizing process in Uberabinha city, today Uberlândia, localized in Triângulo Mineiro. The chosen time frame were 1919 to 1929. In this time was analyzed copies of the newspaper A TRIBUNA. To achieve this goal, the motivating question was to analyze how the advertisements contributed to educate citizens as time that they lived wanted. Then was made a historical journey mapping the history of the Uberabinha city, the emergence of the press and advertisement in Brazil. Then the ads linked to tailors, machinery, services and cars topics were analyzed, to underscore the relevance of scientific discourse that was sustained in the method and technique to teach the citizens in accordance with the civilization and the modern discourse. The advertisements that mention the elements related to health, such as medicines, pills, elixirs were also presented. It is concluded that to civilize a citizen for the challenges of Brazil Republic, were launched many devices beyond formal education, including newspapers and advertisements printed thereon. Through the analysis of various ads, it became clear how the individuals were educated to new sensibilities and new habits. It was also possible to see how the ideals sanitarians imposed new benchmark, and confirmed the principles and ideas of modernity setting new patterns to that rural area. The analysis of advertising\'s principle construction as an element of culture. Thus it can be understood as dialogic and responsive element, in line with the men and the time that produced it, carrying their features. And is the reiteration through the periodicals, the strength of its communication and education.